Penyuluhan Pola Asuh Orang Tua dan Penguatan Karakter Anak Menyongsong Era Disrupsi di Desa Panarian Padang Lawas - Erwin Hamonangan Pane; Nur Hakimah Akhirani Nasution; Kalijunjung Hasibuan; Akhir Saleh Pulungan; Husnia Khotmah Hasibuan; Yusniar Harahap (Jurnal Transformasi Pendidikan Indonesia, 2024)
This activity began with concerns about the high level of smartphone addiction among young children in Panarian Village, Padanglawas Regency. Since people know and use smartphones in Panarian Village in their daily lives, it has had an impact on children's development. Where many parents use smartphones as a tool to help care for fussy children, the result is that many children become addicted and this has an impact on their children's character which is not good. This service activity was carried out using a structured counseling method involving 50 participants consisting of village officials and community representatives who had children aged 2 years to 16 years. To measure the level of success of counseling, pretests and posttests were carried out on activity participants. The results of outreach activities on parenting patterns and strengthening children's character include (1). The knowledge of the community in Panarian Village, Padanglawas Regency regarding parenting patterns is very minimal, as evidenced by the pretest results of 40% of the community having no knowledge of parenting strategies. (2). Counseling participants experienced an increase in knowledge after being given material and simulations by the presenters. This was proven by the results of the postet, which found that 64% of participants were in the very good category in understanding parenting strategies in the digital era. From the results of this activity it can be concluded that the impact of using smartphones as a means of caring for children is very dangerous for children. And through counseling and guidance, parents are aware of the importance of parenting in order to prepare children for good growth and development.